BUILDING WITHOUT ACCOMPANIED BY LAND RIGHT AS FIDUCIARY COLLATERAL OBJECT - Lilawati Ginting; Tan Kamello; Muhammad Yamin; O.K Saidin (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Developing a tourism industry requires substantial funds as business capital. For those who do not possess such funds, they can use a credit facility with collateralfrom the bank. One of the collateral institutions in Indonesia is the fiduciary guaranteewhich is regulated by Law Number 42 of 1999 concerning Fiduciary Guarantee (Fiduciary Law). Based on this Law, buildings can be used as collateral without having to include their land rights. However, there are obstacles in the implementation because to date,proof of ownership of buildings and the occupied land in Indonesia are not separate. This research focuses on the legal certainty of buildings without accompanied by land rights as the fiduciary collateral object. This is normative legal research; legal materials are collected and then analyzed and presented, then further examined to find answers to existing problems. This research concluded that for buildings without land rights to become fiduciary collateral, the government must immediately issue a building ownership certificate /Surat KepemilikanBangunanGedung(SKBG) as mandated by Law Number 28 of 2002 concerning Buildings.